2017
DOI: 10.5455/javar.2017.d189
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of Salmonella serovars in milk and cheese in Mansoura city, Egypt

Abstract: Objective: This study was conducted to determine the prevalence of Salmonella in milk (farm bulk milk, raw market milk) and cheese (kareish, white soft cheese) samples that were collected randomly from farms, supermarkets, small vendors and shops in different districts of Mansoura city, Egypt. Materials and methods: A total of 100 farm bulk milk, raw market milk, kareish cheese and white soft cheese samples (25 of each) were screened for the prevalence of Salmonella spp. The Salmonella isolates were isolated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 30 publications
6
33
1
1
Order By: Relevance
“…85,86 In fact, S. typhimurium is one of the most frequent zoonotic pathogens that causes several human diseases due to consumption of contaminated foods, including meats and raw milk. 87,88 Interestingly, our obtained data from dairy farms showed high prevalence rates of S. typhimurium (26.7%), where there was ascending order of frequency of isolation levels that were 35%, 25%, and 20% from milking utensils, workers' hands swabs, and BTM, respectively. These results are closely correlated with those reported in a previous study where Salmonella spp.…”
Section: Discussionmentioning
confidence: 75%
“…85,86 In fact, S. typhimurium is one of the most frequent zoonotic pathogens that causes several human diseases due to consumption of contaminated foods, including meats and raw milk. 87,88 Interestingly, our obtained data from dairy farms showed high prevalence rates of S. typhimurium (26.7%), where there was ascending order of frequency of isolation levels that were 35%, 25%, and 20% from milking utensils, workers' hands swabs, and BTM, respectively. These results are closely correlated with those reported in a previous study where Salmonella spp.…”
Section: Discussionmentioning
confidence: 75%
“…Various bioactive effects of Aronia melanocarpa (black chokeberry) for improving human's health (Banjari et al, 2017;Jurikova et al, 2017;Sic Zlabur et al, 2017). Nanu et al, 2007;Zeinhom and Abdel-Latef, 2014;El-Baz et al, 2017). In this study, among various foodborne poisoning bacteria, 4 kinds of foodborne poisoning bacteria -Staphylococcus aureus, Cronobacter sakazakii, Salmonella Enteritidis., and Bacillus cereuswhich occur most frequently in milk and dairy products were selected and investigated.…”
Section: Figmentioning
confidence: 76%
“…Especially, the high quality of milk is mainly referred to its composition and hygiene that are provided during the production and storage of milk (El-Baz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murinda et al [29] reported 2.2% of bulk tank milk samples contaminated with Salmonella , attributing the presence of Salmonella in tanks to be the result of cross-contamination from milking environmental sites instead of animal sites. A few recent studies with small sample size indicated Salmonella to be present in raw farm bulk milk at 12% [31]. Results from a similar recent study from Ghana explicated reduced prevalence of Salmonella enterica in cow milk i.e.…”
Section: Discussionmentioning
confidence: 99%